Influencia del peligro y vulnerabilidad en la gestión del riesgo de desastres para el distrito de Jepelacio - Archenti Ruiz, Consuelo (2013)
The present investigation "RISK AND VULNERABILITY INFLUENCE IN THE DISASTERS MANAGEMENT FOR THE JEPELACIO DISTRICT ",emerges from the registration of a flood of the extraordinary and ravines The present investigation «INFLUENCE OF THE DANGER AND VULNERABILITY IN THE MANAGEMENT OF THE RISK OF DISASTERS FOR JEPELACIO's DISTRICT ", Arises from the record ofan extraordinary rise ofthe gullies DISYACU and CROCODILE, Dueto the constant rainfalls generated by regional and local rains with high intensity and frequency~ which they gave origin in order that in the tributary basin tumed into superficial and subsuperficial run-off, it produces precipices of the hillsides with primary and secondary forest in the head-board of the gullies, Due to the constant rainfall generated by local and regional rainfall with high intensity and frequency, which gave rise to tax in the basin has been converted into surface runoff and subsurface, produce landslides on the hillside with primary and secondary forest in the header of the ravines, And the instantaneous extraordinary flows, they dragged sediments and palisades that were forming reservoirs and successive overflows that in his to pass were obstructing the riverbed, producing to him overflows, which in tum have caused destruction of housings and multiple hurts in the infrastructure of Jepelacio1s locality, included bodily injuries with losses oflife. And the extraordinary instant flows, sediments and palizadas dragged that were forming successive dams and flooding in your meditations that were obstructing the riverbed, flooding occur, which in tum has caused destruction of homes and damage multiple in the infrastructure of the town of Jepelacio, including personal injury with loss of life. In this sense, it is vital that we can generate altematives planning, educational and awareness for the local population in order to avoid the disasters that occur on a regular basis; In this sense, it is vital that could generate altematives of planning, educational and of awareness for the local population in order to prevent the disasters from appearing in a frequent way; Likewise to announce that it is of sum of importance the way in which the information gathered in the field of participative form can be translated by means of cartographic Information (maps) by the technologies of analysis and to propose a senes of recommendations, Also to let them know that it is of the utmost importance of the manner in which the information collected in the field of participatory manner can be translated through xi cartographic information (rnaps) with the techniques of analysis and propose a series of recornrnendations, For persons wishing to implement the pmposed methodology can adapt it according to its own characteristics. In the sarne way describes sorne concepts and rnethodology to assess the degree ofthreat or danger, vulnerability and risk. In order that the persons who want to put into practice the proposed methodology could adapt it in conformity with his own characteristics. In the same way sorne concepts and the rnethodology are described to evaluate the degree of threat or of dangerousness, the vulnerability and the risk. The formless present, it seeks to determine the influence of the danger and the vulnerability in the rnanagernent of the risk of disaster, by rneans of the identification of the dangers, the vulnerability, the stratification and the analysis of the dangers to which the district is exposed this way to prornote the rational occupation of the agricultura! and urban soil considering the physical safety of the population. The present report, seeks to determine the influence of risk and vulnerability in disaster risk rnanagernent, through the identification of hazards, vulnerability, stratification, and the analysis of the dangers posed to the district to prornote the rational occupation of the agriculturalland and urban considering the physical security of the population.